Analysis of The Implementation of Halal Product Assurance System Criteria at ABS Restaurant in Bandar Lampung - Febriati, Nurullia; Hidayati, Sri; Winanti, Diki Danar Tri; Herdiana, Novita (JURNAL AGROINDUSTRI HALAL, 2026)
Halal certification plays a vital role in the culinary industry, particularly in regions with a Muslim-majority population, such as Bandar Lampung. The Halal Product Assurance System (SJPH) establishes standards that must be adhered to by business operators, including fast-food restaurants. These operators are obligated to ensure the halal status of their products by fulfilling the criteria outlined in the SJPH to guarantee compliance with halal requirements. This study aims to evaluate the implementation of the SJPH using five criteria in line with the Decree of the Head of the Halal Product Assurance System Organizer No. 57 of 2021. A qualitative research approach was employed, utilizing interviews, observations, and literature reviews for data collection. Findings indicate that the fulfillment of the five SJPH criteria remains inconsistent. Regarding the halal policy, business operators lack a strong commitment to implementation. For materials, traceability for slaughtered products is insufficient. In product processes, there is no established production flow ensuring products are free from impurities (najis). However, in the product aspect, naming practices align with halal assurance criteria. Lastly, the internal audit and management review criteria remain unmet due to limited human resource competence. This study is expected to serve as a reference for business operators, policymakers, consumers, and halal advisory institutions in advancing the implementation of halal certification for restaurants in Bandar Lampung.